EFFECTS OF AGRICULTURAL PRACTICE ON THE WATER QUALITY OF LOW-ORDER STREAMS IN THE BEAVER VALLEY WATERSHED - Dieleman, Catherine M. (My University, 2012)
Eutrophication from agricultural runoff is a global issue, and can often result in degradation and loss of aquatic habitat. The overall objective of this study is to gain a better understanding of the factors that influence variation in water chemistry of low-order streams in an agricultural watershed. The first chapter finds significant differences between the effects of livestock- vs and crop-based operations on water chemistry while modeling the relationship between independent landscape variables and major water-quality parameters in an agroecosystem. I also determine significant differences exist in dependent variables among seasons and are best described by the agriculturally relevant calendar (ARC). In Chapter 2, I compared the effectiveness of discrete and continuous sampling programs for monitoring the impacts of cattle disturbances on water quality. I found that daily total phosphorus (TP) concentrations (integrated sample taken every 6 hours) were not significantly correlated with precipitation and were significantly lower than discrete water samples. Turbidity readings (recorded every half hour) showed spikes that corresponded with cattle hydration events and increased levels of nutrients through backwash. . In Chapter 3, I find a significant relationship between periphyton growth and the level of primary nutrients (TP, soluble reactive phosphorus, total-ammonia nitrogen). Thus, for low-order streams influenced by small family farms, acrylic rods may be an inexpensive indicator of excess limiting nutrients. In such environments stream length may be a stronger measure of streams than stream order since total nitrogen, TP and pH were significantly correlated with stream length.
Keywords: agriculture; low-order streams; water chemistry; algae; eutrophication; livestock; storm events; periphyton; stream order; Agriculture; Agriculture